Hubungan Antara Dukungan Sosial Pengasuh dengan Kemandirian Emosional Anak Asuh di Panti Asuhan Penuh Pengharapan Kota Medan - Ela Saputri; Yusnadi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to determine the level of caregiver social support, the level of emotional autonomy of foster children, and the relationship between caregiver social support and emotional autonomy of foster children at Panti Asuhan Penuh Pengharapan, Medan City. This research used a quantitative approach with a correlational method. The population consisted of 23 foster children, and all members of the population were selected as the research sample using total sampling technique. Data were collected through caregiver social support questionnaires and emotional autonomy questionnaires that had been tested for validity and reliability. Data analysis techniques used tendency analysis and Pearson Product Moment correlation assisted by SPSS version 20. The results showed that caregiver social support was in the moderate category with a percentage of 56.5%, while the emotional autonomy of foster children was also in the moderate category with a percentage of 47.8%. The Pearson Product Moment correlation test obtained a correlation coefficient of 0.579 with a significance value of 0.004 (p < 0.05). These results indicate that there is a positive and significant relationship between caregiver social support and emotional autonomy of foster children at Panti Asuhan Penuh Pengharapan, Medan City. The better the social support provided by caregivers, the better the emotional autonomy of foster children